Composite-phase ternary positive electrode material and preparation method and application thereof
By adopting the preparation method of composite phase ternary positive electrode material in the lithium-ion battery positive electrode material, combined with the steps of sintering, calcining, ion exchange and coating, the problem of insufficient capacity and circulation performance of the positive electrode material in the prior art is solved, and the battery performance with high specific capacity, excellent Coulomb efficiency and long cycle life is achieved.
Patent Information
- Application Number
- CN202411742604.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art has shortcomings in improving the capacity and cycle performance of the positive electrode material of lithium-ion battery, especially under high charging cutoff voltage, the instability of the O3 phase structure material and the high cost and insufficient performance of lithium cobalt oxide.
By adopting the preparation method of composite phase ternary positive electrode material, the precursor of the ternary positive electrode material is mixed with a lithium source, then mixed with a sodium source and a cobalt source to calcinate, and then ion exchange reaction is carried out to form a composite phase in which O2 and O3 coexist, and then sintered after coating, the structural stability and electrical properties of the material are improved.
The high specific capacity, excellent Coulomb efficiency and long cycle life of the composite phase ternary cathode material are achieved, which avoids the disadvantages brought about by the complexity of embedded sodium ions, ensures the stability of the material under high voltage conditions, and improves the overall performance of the battery.
Smart Images

Figure CN119560533A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a composite phase ternary positive electrode material and a preparation method and application thereof. Background Art
[0002] Currently, the market's requirements for the energy density of lithium-ion batteries are constantly increasing, and a method to improve the energy density of lithium-ion batteries is urgently needed.
[0003] Lithium cobalt oxide can provide batteries with high energy density, but as the charging cut-off voltage of lithium cobalt oxide increases, the O3 phase structure material will be very unstable under ultra-high charging cut-off voltage. At present, some researchers have mixed O2 phase materials and O3 phase materials in a certain proportion to improve the capacity and cycle stability of positive electrode materials. However, after all, the disadvantages of O3 phase materials under high charging cut-off voltage will become more and more obvious with the increase of cycle times, and the capacity attenuation will increase under long cycles, resulting in poor battery performance. Some scholars also directly sintered compounds containing sodium elements and exchanged ions with lithium elements, and directly used lithium cobalt oxide as the positive electrode, but there are problems such as high cost of lithium cobalt oxide and inferior capacity performance and cycle performance to ternary positive electrode materials. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the prior art in insufficiently improving the capacity and cycle performance of positive electrode materials, thereby providing a composite phase ternary positive electrode material and a preparation method and application thereof.
[0005] To this end, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a composite phase ternary positive electrode material, wherein the preparation method comprises the following steps:
[0007] S1, mixing a ternary cathode material precursor with a first lithium source, and sintering the mixture to obtain a sintered product;
[0008] S2, mixing the first calcined product, the sodium source and the cobalt source, and calcining the mixture to obtain a second calcined product;
[0009] S3, mixing the second calcined product and the second lithium source, and performing an ion exchange reaction to obtain a composite phase ternary positive electrode material.
[0010] In the present invention, XRD test is carried out to prove the existence of O2 and O3 composite phases.
[0011] In the present invention, the first lithium source and the second lithium source are conventional lithium sources in the art. Typically, but not limiting, the first lithium source and the second lithium source each independently include at least one of lithium carbonate and lithium hydroxide;
[0012] In the present invention, the molar ratio of the lithium element in the lithium source to the total metal elements in the ternary positive electrode material precursor is 1.04-1.06:1; the metal elements in the ternary positive electrode material precursor refer to nickel, cobalt and manganese.
[0013] In the present invention, the mixing is conventional mixing in the art, and it only needs to be able to mix evenly.
[0014] According to the present invention, the sintering conditions include: a sintering temperature of 900-1000° C., and a sintering time of 8-12 hours; the calcining conditions include: a calcining temperature of 600-750° C., and a calcining time of 6-10 hours.
[0015] According to the present invention, after the ion exchange reaction, the ion exchange product is mixed with a coating agent, and then sintered after coating.
[0016] In the present invention, the sintering after coating is conventional sintering in the art. Typically, but not limiting, the conditions for sintering after coating include: a sintering temperature of 300-500° C., and a sintering time of 4-8 hours.
[0017] According to the present invention, the molar ratio of the sum of the metal elements in the ternary cathode material precursor to the sum of the metal elements in the coating agent is 1:0.001-0.006.
[0018] According to the present invention, the coating agent includes at least one of an aluminum source and a tungsten source.
[0019] According to the present invention, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide or aluminum inorganic salt; further optionally, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate.
[0020] According to the present invention, the tungsten source includes at least one of tungsten oxide, tungsten acid or tungstate; further optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid and ammonium paratungstate.
[0021] According to the present invention, when the coating agent is an aluminum source and a tungsten source, the molar ratio of the aluminum element in the aluminum source to the tungsten element in the tungsten source is (2-5):1.
[0022] According to the present invention, in S2, the molar ratio of the sum of metal ions in the ternary positive electrode material precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source is 1:(0.007-0.012):(0.01-0.015).
[0023] According to the present invention, the sodium source includes sodium salt and / or sodium alkali; further optionally, the sodium source includes at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide.
[0024] According to the present invention, the cobalt source includes at least one of cobalt-containing oxides, cobalt oxyhydroxides, and cobalt-containing hydroxides; further optionally, the cobalt source includes at least one of cobalt oxide, cobalt oxyhydroxide, and cobaltous hydroxide.
[0025] According to the present invention, the molar ratio of the lithium element in the second lithium source to the sodium element in the sodium source is 1-10:1.
[0026] According to the present invention, the conditions of the ion exchange reaction include: the temperature of the ion exchange reaction is 200-400° C., and the time is 1-8 hours.
[0027] According to the present invention, the temperature of the ion exchange reaction is 250-380° C. and the time is 2-6 hours.
[0028] The second aspect of the present invention protects a composite phase ternary positive electrode material obtained by the aforementioned preparation method.
[0029] A third aspect of the present invention protects a secondary battery, wherein the secondary battery comprises the aforementioned composite phase ternary positive electrode material.
[0030] In the present invention, the battery preparation method is as follows: positive electrode material, polyvinylidene fluoride (PVDF), acetylene black are mixed with N-methylpyrrolidone (NMP) in a mass ratio of 96: (2-2.5): (2-2.5), wherein the mass ratio of solid to liquid is 7: 2.5-3.5, to prepare positive electrode slurry; negative electrode material graphite, binder LA133 and carbon nanotubes CNT are mixed evenly in a mass ratio of 92: (5-6): (2-2.5) to prepare mixed negative electrode slurry, and then the positive and negative electrode slurries are subjected to the processes of coating-rolling-slicing-winding-assembly-liquid injection-formation-secondary sealing-capacity division to prepare finished soft-pack batteries.
[0031] The technical solution of the present invention has the following advantages:
[0032] 1. The present invention provides a method for preparing a composite phase ternary positive electrode material, wherein the preparation method comprises the following steps: S1, mixing a ternary positive electrode material precursor with a first lithium source, sintering, and obtaining a first sintered product; S2, mixing the first sintered product, a sodium source, and a cobalt source, calcining, and obtaining a second sintered product; S3, mixing the second sintered product and a second lithium source, performing an ion exchange reaction, and obtaining a composite phase ternary positive electrode material; wherein the first sintered product is an O3 phase, after adding a sodium source and a cobalt source, the sodium source and the cobalt source will exist as coating materials on the interface of the O3 phase, and then form a P2 phase coating material on the interface of the O3 phase material, and then perform an ion exchange reaction, lithium ions and sodium ions exchange ions, and obtain a phase where O3 and O2 coexist, because sodium ions and lithium ions The radius of sodium ions is different. The radius of sodium ions is about 25% larger than that of lithium ions, which makes the embedding and extraction process of sodium ions in the material more complicated. After ion exchange, the new radius of the material level is adjusted to adapt to the lithium ions, avoiding the disadvantages brought by sodium ions. During use, after high voltage is applied to dissolve lithium ions, the positive electrode material structure that adapts to lithium ions still maintains the stability of the coexistence phase of O3 and O2 after the lithium ions are separated, ensuring the structural stability of the material. In addition, the presence of the O2 phase can effectively alleviate the dissolution of metal ions and avoid strong redox reactions in the interface layer, thereby improving the stability of the battery positive electrode material interface. The O2 phase can also accelerate the transmission of lithium ions, so that the positive electrode material exhibits excellent specific capacity, coulombic efficiency and cycle performance.
[0033] 2. The present invention adds a coating agent to coat the ion exchange product, isolate the electrolyte, and further improve the electrical properties of the positive electrode material.
[0034] 3. In the present invention, the specific molar ratio of the sum of metal elements in the ternary positive electrode material precursor and the sum of metal elements in the coating agent, the specific type of the coating agent, the specific molar ratio of the sum of metal ions in the ternary positive electrode material precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source, and the specific types of the sodium source and the cobalt source can further improve the specific capacity, coulombic efficiency and cycle performance of the positive electrode material.
[0035] 4. The specific conditions of ion exchange in the present invention can further optimize the reaction effect, thereby further improving the electrical properties of the prepared positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 is the XRD image of the composite phase ternary cathode material prepared in Example 1;
[0038] Figure 2 This is an electron microscope image of the composite phase ternary positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0039] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0041] Example 1
[0042] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0043] S1, mixing the ternary cathode material precursor and lithium carbonate, sintering, and obtaining a lithium ion battery with a chemical formula of Li 1.04 Ni 0.60 Co 0.10 Mn 0.30 O2 a sintered product; the molar ratio of lithium in lithium carbonate to the sum of metal elements of nickel, cobalt and manganese in the ternary cathode material precursor is 1.04:1; sintering is carried out in an oxygen atmosphere at a sintering temperature of 940°C for 10 hours;
[0044] S2, mixing the first calcined product, cobaltous hydroxide and sodium carbonate, and calcining to obtain a second calcined product; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.009:0.013; the calcination is carried out in an oxygen atmosphere, the calcination temperature is 750°C, and the time is 8 hours;
[0045] S3, mixing the calcined product and lithium hydroxide, and performing an ion exchange reaction to obtain an ion exchange product; wherein the molar ratio of the lithium element in the lithium hydroxide to the sodium element in the sodium carbonate is 3:1; the temperature of the ion exchange reaction is 280° C., and the time is 3 hours;
[0046] S4, mixing the ion exchange product, the coating agent aluminum oxide and tungsten oxide, coating and sintering to obtain a composite phase ternary positive electrode material; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of the metal elements in the coating agent is 1:0.004, the molar ratio of the aluminum element and the tungsten element in the coating agent is 3:1, and the coating and sintering are carried out in an oxygen atmosphere at a temperature of 400°C and a time of 6 hours; the XRD image of the composite phase ternary positive electrode material is as follows Figure 1 As shown, Figure 1 It can be seen that O3 and O2 composite phases are generated. The position of the diffraction peak of the O2 phase corresponds to the standard card PDF#54-0894, and the position of the diffraction peak of the O3 phase corresponds to the standard card PDF#85-1979. The electron microscope image of the composite phase ternary cathode material is as follows: Figure 2 As shown, from Figure 2 It can be seen that the single crystal particles of the positive electrode material are full, the interface is smooth and easy to disperse.
[0047] Example 2
[0048] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0049] S1, mixing the ternary cathode material precursor and lithium carbonate, sintering, and obtaining a lithium ion battery with a chemical formula of Li 1.04 Ni 0.60 Co 0.10 Mn 0.30 O2 sintering product; the molar ratio of lithium element in lithium carbonate and the sum of metal elements of nickel element, cobalt element and manganese element in the ternary positive electrode material precursor is 1.05:1; sintering is carried out in an oxygen atmosphere, the sintering temperature is 950°C, and the time is 10h;
[0050] S2, mixing the first calcined product, cobaltous hydroxide and sodium carbonate, and calcining to obtain a second calcined product; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.009:0.013; the calcination is carried out in an oxygen atmosphere, the calcination temperature is 700°C, and the time is 8 hours;
[0051] S3, mixing the calcined product and lithium hydroxide, and performing an ion exchange reaction to obtain an ion exchange product; wherein the molar ratio of the lithium element in the lithium hydroxide to the sodium element in the sodium carbonate is 4:1; the temperature of the ion exchange reaction is 280° C., and the time is 2 hours;
[0052] S4, mixing the ion exchange product, coating agent aluminum oxide and tungsten oxide, coating and sintering to obtain a composite phase ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0036, the molar ratio of aluminum element to tungsten element in the coating agent is 2:1, and the sintering after coating is carried out in an oxygen atmosphere at a temperature of 450°C for 6 hours.
[0053] Example 3
[0054] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0055] The method of Example 1 is the same, except that step S4 is omitted, and the obtained ion exchange product is a composite phase ternary positive electrode material.
[0056] Example 4
[0057] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0058] The method of Example 1 is the same, except that in S4, the ion exchange product, alumina and alumina are mixed, coated and sintered to obtain a composite phase ternary positive electrode material; wherein the molar ratio of the sum of metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the sum of metal elements in the coating agent is 1:0.004, and the molar ratio of aluminum and tungsten in the coating agent is 3:1.
[0059] Example 5
[0060] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0061] The method of Example 1 is different in that in S4, the coating agent is tungsten oxide, and the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor to the tungsten element in tungsten oxide is 1:0.004.
[0062] Example 6
[0063] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0064] The method of Example 1 is different in that, in S2, the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate and the cobalt element in cobaltous hydroxide is 1:0.01:0.012.
[0065] Example 7
[0066] This embodiment provides a method for preparing a composite phase ternary positive electrode material, which is as follows:
[0067] The method of Example 1 is the same, except that in S2, the temperature of the ion exchange reaction is 200° C. and the time is 1 hour.
[0068] Comparative Example 1
[0069] This comparative example provides a method for preparing a ternary positive electrode material, which is as follows:
[0070] The ternary cathode material precursor is mixed with lithium carbonate and sintered to obtain a lithium ion battery with the chemical formula Li 1.04 Ni 0.60 Co 0.10 Mn 0.30 O2 a sintered product; the molar ratio of the lithium element in the lithium carbonate to the total metal elements of the nickel element, the cobalt element, and the manganese element in the ternary positive electrode material precursor is 1.04:1; the sintering is carried out in an oxygen atmosphere at a sintering temperature of 940°C for 10 hours to obtain a ternary positive electrode material.
[0071] Comparative Example 2
[0072] This comparative example provides a method for preparing a ternary positive electrode material, which is as follows:
[0073] S1, mixing the ternary cathode material precursor and lithium carbonate, sintering, and obtaining a lithium ion battery with a chemical formula of Li 1.04 Ni 0.60 Co 0.10 Mn 0.30 O2 a sintered product; the molar ratio of lithium in lithium carbonate to the sum of metal elements of nickel, cobalt and manganese in the ternary cathode material precursor is 1.04:1; sintering is carried out in an oxygen atmosphere at a sintering temperature of 940°C for 10 hours;
[0074] S2, mixing the first calcined product, cobaltous hydroxide and sodium carbonate, and calcining to obtain a second calcined product; wherein the molar ratio of the sum of the metal elements of nickel, cobalt and manganese in the ternary positive electrode material precursor, the sodium element in sodium carbonate, and the cobalt element in cobaltous hydroxide is 1:0.009:0.013; the calcination is carried out in an oxygen atmosphere, the calcination temperature is 750°C, and the time is 8 hours to obtain a ternary positive electrode material.
[0075] Test Case
[0076] The battery preparation method is as follows: the positive electrode material, polyvinylidene fluoride (PVDF) and acetylene black prepared in the embodiment and the comparative example are mixed with N-methylpyrrolidone (NMP) in a mass ratio of 96:2:2, wherein the mass ratio of solid to liquid is 7:3, to prepare a positive electrode slurry; the negative electrode material graphite, the binder LA133 and the carbon nanotube CNT are evenly mixed in a mass ratio of 92:6:2 to prepare a mixed negative electrode slurry; and the positive and negative electrode slurries are subjected to the processes of coating-rolling-slicing-winding-assembly-liquid injection-formation-secondary sealing-capacity division to prepare a finished soft-pack battery.
[0077] At 25°C, the battery was charged to 4.5V at a rate of 0.1C to obtain the first charge specific capacity; then discharged to 3V at a rate of 0.1C to obtain the first discharge specific capacity; the first coulombic efficiency was the first charge specific capacity / first discharge specific capacity × 100%;
[0078] At 45°C, the battery is charged to 4.5V at a rate of 0.5C, and then discharged to 3V at a rate of 0.5C for 500 cycles. The capacity retention rate of the Xth week = the discharge specific capacity of the Xth week / the discharge specific capacity of the first week) × 100%, where X = 100, 200, 300, 400 or 500;
[0079] The specific test results are shown in Table 1
[0080] Table 1
[0081]
[0082] The battery of the composite phase ternary positive electrode material prepared by the invention has excellent specific capacity, coulombic efficiency and cycle performance.
[0083] Comparison of the embodiment with the comparative example shows that the electrical properties of the positive electrode material are improved after the phase transformation treatment.
[0084] Comparing Example 1 with Example 7, it can be seen that the specific conditions of ion exchange can further optimize the effect, thereby further improving the electrical properties of the prepared positive electrode material.
[0085] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a composite phase ternary positive electrode material, characterized in that: The preparation method comprises the following steps: S1, mixing a ternary cathode material precursor with a first lithium source, and sintering the mixture to obtain a sintered product; S2, mixing the first calcined product, the sodium source and the cobalt source, and calcining the mixture to obtain a second calcined product; S3, mixing the second calcined product and the second lithium source, and performing an ion exchange reaction to obtain a composite phase ternary positive electrode material.
2. The preparation method according to claim 1, characterized in that: After the ion exchange reaction, the method further comprises mixing the ion exchange product with a coating agent, coating the product and then sintering the product.
3. The preparation method according to claim 2, characterized in that: The molar ratio of the total amount of metal elements in the ternary positive electrode material precursor to the total amount of metal elements in the coating agent is 1:0.001-0.
006.
4. The preparation method according to claim 2, characterized in that: The coating agent includes at least one of an aluminum source and a tungsten source; Optionally, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide or aluminum inorganic salt; further optionally, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum sulfate, aluminum chloride and aluminum nitrate; Optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid or tungstate; further optionally, the tungsten source includes at least one of tungsten oxide, tungstic acid and ammonium paratungstate; Optionally, when the coating agent is an aluminum source and a tungsten source, the molar ratio of the aluminum element in the aluminum source to the tungsten element in the tungsten source is (2-5):
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the sum of metal ions in the ternary positive electrode material precursor, the sodium element in the sodium source, and the cobalt element in the cobalt source is 1:(0.007-0.012):(0.01-0.015).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The sodium source includes sodium salt and / or sodium alkali; further optionally, the sodium source includes at least one of sodium carbonate, sodium bicarbonate and sodium hydroxide; Optionally, the cobalt source includes at least one of cobalt-containing oxides, cobalt oxyhydroxides, and cobalt-containing hydroxides; further optionally, the cobalt source includes at least one of cobalt oxide, cobalt oxyhydroxide, and cobaltous hydroxide.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The molar ratio of the lithium element in the second lithium source to the sodium element in the sodium source is 1-10:
1.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering conditions include: a sintering temperature of 900-1000°C and a sintering time of 8-12h; And / or, the calcination conditions include: the calcination temperature is 600-750°C, and the calcination time is 6-10h; And / or, the conditions of the ion exchange reaction include: the temperature of the ion exchange reaction is 200-400° C., and the time is 1-8 h; Optionally, the ion exchange reaction is carried out at a temperature of 250-380° C. and for a time of 2-6 hours.
9. A composite phase ternary positive electrode material obtained by the preparation method according to any one of claims 1 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises the composite phase ternary positive electrode material according to claim 9.